2007
DOI: 10.1128/jvi.01820-06
|View full text |Cite
|
Sign up to set email alerts
|

Hijacking Components of the Cellular Secretory Pathway for Replication of Poliovirus RNA

Abstract: Infection of cells with poliovirus induces a massive intracellular membrane reorganization to form vesiclelike structures where viral RNA replication occurs. The mechanism of membrane remodeling remains unknown, although some observations have implicated components of the cellular secretory and/or autophagy pathways. Recently, we showed that some members of the Arf family of small GTPases, which control secretory trafficking, became membrane-bound after the synthesis of poliovirus proteins in vitro and associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
179
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(192 citation statements)
references
References 47 publications
(57 reference statements)
8
179
3
2
Order By: Relevance
“…These data indicate that de novo expression of PRL-3, as seen in many forms of cancer, stimulates turnover by functionally hijacking BFA-sensitive Arf1 activation to the turnover machinery of integrins. It is increasingly appreciated that proteins that are expressed in cancer can act in signaling cascades otherwise not influenced by their presence due to subcellular sequestration (Belov et al, 2007). Our data showing that PRL-3 and activated Arf1 are recruited to intracellular membranes strongly support this hypothesis.…”
Section: Discussionsupporting
confidence: 78%
“…These data indicate that de novo expression of PRL-3, as seen in many forms of cancer, stimulates turnover by functionally hijacking BFA-sensitive Arf1 activation to the turnover machinery of integrins. It is increasingly appreciated that proteins that are expressed in cancer can act in signaling cascades otherwise not influenced by their presence due to subcellular sequestration (Belov et al, 2007). Our data showing that PRL-3 and activated Arf1 are recruited to intracellular membranes strongly support this hypothesis.…”
Section: Discussionsupporting
confidence: 78%
“…There are two types of well-defined families of PI4Ks, type II (PI4KIIa and PI4KIIb) and type III (PI4KIIIa and PI4KIIIb). Previous studies on PV and CVB3 have identified PI4KIIIb as the host enzyme upregulated in viral replication factories (Arita et al, 2011;Belov et al, 2007;Hsu et al, 2010;Lanke et al, 2009). Depletion of PI4KIIIb activity within infected cells by RNA silencing or the use of kinase inhibitors, such as PIK93 (Knight et al, 2006), appeared to block PV and CVB3 viral RNA synthesis and virus replication.…”
Section: Introductionmentioning
confidence: 99%
“…The targeting of host factors associated with viral replication complexes (VRCs) such as ADP-ribosylation factor 1 (ARF1), guanine nucleotide exchange factor 1 (GBF1) and phosphatidylinositol kinase 4III (PI4IIIKα/β) has also been shown to inhibit the replication of HCV, several enteroviruses such as picornavirus (PV), Aichi virus (AiV) and Coxsackie virus B3 (CVB3), as well as rhinovirus, mouse hepatitis coronavirus (MHV) and HIV-1 81,[93][94][95][96][97][98][99][100][101] .Some viruses such as DENV and HCV are known to induce up-regulation of lipid synthesis for their replication 54 . Lipid rafts are described to be involved in entry, assembly and/or budding of influenza virus, HCV, VSV, HIV-1, Epstein Barr virus (EBV), Ebola virus (EBOV), Marburg virus (MARV), DENV, West Nile virus (WNV) and Herpes Simplex virus (HSV) ( Table 2).…”
Section: Targeting Common Host-factors Used For Viral Replicationmentioning
confidence: 99%